For this case we must find an equation, whose solutions are given by:
![x = 2\\x = -3](https://img.qammunity.org/2020/formulas/mathematics/high-school/xn9ak12ohvabsb2oeqdlulety3ibxuek6i.png)
Or equivalently:
![(x-2) (x + 3) = 0](https://img.qammunity.org/2020/formulas/mathematics/high-school/pgto8vicj4sgigwm4qt2kgguo8qoqdlovq.png)
Applying distributive property we have:
![x ^ 2 + 3x-2x-6 = 0\\x ^ 2 + x-6 = 0](https://img.qammunity.org/2020/formulas/mathematics/high-school/h6vav7fafiukb8cfqs6id6x9r8ira44mnp.png)
Now, if we multiply both sides of the equation by 2, we have:
![2x ^ 2 + 2x-12 = 0](https://img.qammunity.org/2020/formulas/mathematics/high-school/jn80fatrp7pil8jfsz3loequ7xsdk7ovhp.png)
Thus, the equation that has the solution
is:
![2x ^ 2 + 2x-12 = 0](https://img.qammunity.org/2020/formulas/mathematics/high-school/jn80fatrp7pil8jfsz3loequ7xsdk7ovhp.png)
Answer:
![2x ^ 2 + 2x-12 = 0](https://img.qammunity.org/2020/formulas/mathematics/high-school/jn80fatrp7pil8jfsz3loequ7xsdk7ovhp.png)
Option D